Candida albicans Isolates from the Gut of Critically Ill Patients Respond to Phosphate Limitation by Expressing Filaments and a Lethal Phenotype - Romanowski, Kathleen (Public Library of Science, 2012)
Candida albicans is an opportunistic pathogen that proliferates in the intestinal tract of critically ill patients where it continues to be a major cause of infectious-related mortality. The precise cues that shift intestinal C. albicans from its ubiquitous indolent colonizing yeast form to an invasive and lethal filamentous form remain unknown. We have previously shown that severe phosphate depletion develops in the intestinal tract during extreme physiologic stress and plays a major role in shifting intestinal Pseudomonas aeruginosa to express a lethal phenotype via conserved phosphosensory-phosphoregulatory systems. Here we studied whether phosphate dependent virulence expression could be similarly demonstrated for C. albicans. C. albicans isolates from the stool of critically ill patients and laboratory prototype strains (SC5314, BWP17, SN152) were evaluated for morphotype transformation and lethality against C. elegans and mice during exposure to phosphate limitation. Isolates ICU1 and ICU12 were able to filament and kill C. elegans in a phosphate dependent manner. In a mouse model of intestinal phosphate depletion (30% hepatectomy), direct intestinal inoculation of C. albicans caused mortality that was prevented by oral phosphate supplementation. Prototype strains displayed limited responses to phosphate limitation; however, the pho4Δ mutant displayed extensive filamentation during low phosphate conditions compared to its isogenic parent strain SN152, suggesting that mutation in the transcriptional factor Pho4p may sensitize C. albicans to phosphate limitation. Extensive filamentation was also observed in strain ICU12 suggesting that this strain is also sensitized to phosphate limitation. Analysis of the sequence of PHO4 in strain ICU12, its transcriptional response to phosphate limitation, and phosphatase assays confirmed that ICU12 demonstrates a profound response to phosphate limitation. The emergence of strains of C. albicans with marked responsiveness to phosphate limitation may represent a fitness adaptation to the complex and nutrient scarce environment typical of the gut of a critically ill patient.